Perancangan dan Pengembangan Sistem Smart Parking Berbasis ESP32 dan Aplikasi Mobile Android Studio - Erick; Maxi Yuvier; Nelson Fernando; Ng Marcelleno; Andik Yulianto (Universitas Internasional Batam, 2025)
The rapid growth in the number of vehicles has intensified challenges in parking management, leading to traffic congestion and wasted time for drivers searching for available spots. Conventional parking systems, which often rely on manual processes, are inefficient and contribute to these problems. This research addresses these issues by designing and developing an Internet of Things (IoT) based smart parking system to provide real-time monitoring of parking availability. The system utilizes an ESP32 microcontroller, chosen for its integrated Wi-Fi and processing capabilities, as the core processing unit. For vehicle and user management, an RFID-RC522 sensor is used for vehicle entry authentication , while an HC-SR04 ultrasonic sensor detects vehicles at the exit. The backend architecture employs a multi-layered approach, using MQTT as the communication protocol with HiveMQ as the broker. System logic and data flows are managed using Node-RED, which communicates with a Flask server to interact with the database. The user interface is a mobile application developed using Android Studio. This application requires user authentication via a login page and provides a real-time dashboard that visually displays the status of parking slots—green for available and red for occupied. The successful implementation of this prototype demonstrates a functional end-to-end solution that effectively integrates hardware and software to create a more efficient and user-friendly parking management system.